Quantification of soy protein using the isotope method (δ13C and δ15N) for commercial brands of beef hamburger - Ducatti, Rhani [UNESP]; de Almeida Nogueira Pinto, José Paes [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Ducatti, Carlos [UNESP] (Elsevier, 2016)
Hamburgers (beef patties) may be adulterated through the overuse of protein extenders. Among vegetables, soy protein is the best substitute for animal protein. These ingredients help to reduce the cost of producing a final product, and they maximize profits for fraudulent industries. Moreover, the ingestion of soy or other non-meat proteins by allergic individuals may present a health risk. In addition, monitoring by supervisory bodies is hampered by a lack of appropriate analytical methodologies. Within this context, the aim of this study was to determine and quantify the levels of added soy protein by determination of 15N and 13C stable isotopes. A total of 100 beef hamburger samples from 10 commercial brands were analyzed. Only three samples of the G brand were within the standards set the Brazilian legislation. The remaining 97 samples from 10 commercial brands contained > 4% soy protein; therefore, they are adulterated and not in compliance with the current legislation.
Keywords: Adulteration; Hamburger meat; Soy protein; Stable isotopes